2014
DOI: 10.1016/j.jep.2013.11.057
|View full text |Cite
|
Sign up to set email alerts
|

New finding of an anti-TB compound in the genus Marsypopetalum (Annonaceae) from a traditional herbal remedy of Laos

Abstract: Ethnopharmacological relevance There is widespread use of traditional herbal remedies in the Lao PDR (Laos). It is common practice to treat many diseases with local plants. This research project documented and analysed some of these traditional remedies used to treat symptoms of tuberculosis (TB). Materials and methods This research was executed by interviewing healers about plants used traditionally to treat the symptoms of TB. Samples of some of the plants were collected, and extracts of 77 species were su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…3-α-tigloyl-melianol has no toxicity on Vero cells which is very important for further research [16]. [5][6][7][8] South America is another huge area where folk medicine is the main treatment. Allophylus edulis is an endemic plant of the region which is commonly known as a good anti-inflammatory remedy.…”
Section: Extracts and Natural Substances Isolated From Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…3-α-tigloyl-melianol has no toxicity on Vero cells which is very important for further research [16]. [5][6][7][8] South America is another huge area where folk medicine is the main treatment. Allophylus edulis is an endemic plant of the region which is commonly known as a good anti-inflammatory remedy.…”
Section: Extracts and Natural Substances Isolated From Plantsmentioning
confidence: 99%
“…A similar situation exists in Laos, where healers use 77 various plants, of which only 10% display any anti-mycobacterial activity. The most potent seems to be Marsypopetalum modestum MIC from 1.33-23.52 µg/ml [6]. A review of folk medicine plants from Southeast Asia shows that 24.2% of extract from 132 species used in ethnomedicine have significant anti-mycobacterial activity (MIC less than 100 µg/ml).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the initial primary screening results are presented in a paper by Elkington et al ( 2014b ).…”
Section: Primary Evaluation Protocolmentioning
confidence: 99%
“…The collection numbers in parentheses represent the voucher herbarium specimen numbers. All extracts were tested at 100 μg/mL a Recollections of species marked by an asterisk did not exhibit activity in the bioassays 3 Biochemical Validation ( 2009 ), where the spelling for the common name is Tin Tang Teeyah and the taxonomic identity was Polyalthia sp., and later, when the spelling for the common name was changed to Tin Tang Tia and the taxonomic identity was determined to be a Marsypopetalum species (Elkington et al 2014b ).…”
Section: All Species Evaluatedmentioning
confidence: 99%
“…Some preliminary research reported the activity of T. crispa against M. tuberculosis. Ethanolic extract of T. crispa from Laos has antimycobacterial activity against M. tuberculosis with minimum inhibitory concentration (MIC) 2,43 -96,2 µg/ml (Elkington et al, 2014). But there has been no report about the antimycobacterial activity of T. crispa that grows in Indonesia and its fractions or isolates.…”
Section: Introductionmentioning
confidence: 99%